p70 Ribosomal Protein S6 Kinase Is a Checkpoint of Human Hepatic Stellate Cell Activation and Liver Fibrosis in MiceSummary - Florian P. Reiter (Elsevier, 2022)
Background & Aims: Progression of chronic liver disease (CLD) to liver cirrhosis and liver cancer is a major global cause of morbidity and mortality. Treatment options capable of inhibiting progression of liver fibrosis when etiological treatment of CLD is not available or fails have yet to be established. We investigated the role of serine/threonine kinase p70 ribosomal protein S6 kinase (p70S6K) as checkpoint of fibrogenesis in hepatic stellate cells (HSCs) and as target for the treatment of liver fibrosis. Approach & Results: Immunohistochemistry was used to assess p70S6K expression in liver resection specimen. Primary human or murine HSCs from wild-type or p70S6K–/– mice as well as LX-2 cells were used for in vitro experiments. Specific small interfering RNA or CEP-1347 were used to silence or inhibit p70S6K and assess its functional relevance in viability, contraction and migration assays, fluorescence-activated cell sorting, and Western blot. These results were validated in vivo by a chemical model of fibrogenesis using wild-type and p70S6K–/– mice. Expression of p70S6K was significantly increased in human cirrhotic vs noncirrhotic liver-tissue and progressively increased in vitro through activation of primary human HSCs. Conversely, p70S6K induced fibrogenic activation of HSCs in different models, including the small interfering RNA–based silencing of p70S6K in HSC lines, experiments with p70S6K–/– cells, and the pharmacological inhibition of p70S6K by CEP-1347. These findings were validated in vivo as p70S6K–/– mice developed significantly less fibrosis upon exposure to CCl4. Conclusions: We establish p70S6K as a checkpoint of fibrogenesis in vitro and in vivo and CEP-1347 as potential treatment option that can safely be used for long-term treatment.